Towards flexible automated support to improve the quality of computational science and engineering software - Falessi, Davide; Shull, Forrest (2013 5th International Workshop on Software Engineering for Computational Science and Engineering (SE-CSE) : proceedings : May 18, 2013, San Francisco, CA, USA, 2013)
Continual evolution of the available hardware (e.g. in terms of increasing size, architecture, and computing power) and software (e.g. reusable libraries) is the norm rather than exception. Our goal is to enable CSE developers to spend more of their time finding scientific results by capitalizing on these evolutions instead of being stuck in fixing software engineering (SE) problems such as porting the application to new hardware, debugging, reusing (unreliable) code, and integrating open source libraries. In this paper we sketch a flexible automated solution supporting scientists and engineers in developing accurate and reliable CSE applications. This solution, by collecting and analyzing product and process metrics, enables the application of well-established software engineering best practices (e.g., separation of concerns, regression testing and inspections) and it is based upon the principles of automation, flexibility and iteration.